(untitled) (Scientific journal of the Fergana State University, 2025)
Comprehension skills encompass the cognitive processes and strategies individuals use to understand, interpret, and derive meaning from various forms of information, including text, spoken language, and visual representations. These skills are essential for effective learning and communication, requiring active engagement to construct mental representations and make sense of encountered material. Key components include decoding and vocabulary knowledge, understanding text structures, making inferences, activating background knowledge, critical thinking, and integration of information across contexts. Assessing learners’ comprehension skills involves evaluating their ability to understand main ideas, infer relationships, and analyze or synthesize content from diverse sources. Instruction tailored to these components can enhance comprehension abilities, fostering critical thinking and meaningful learning. By exploring these facets, educators can create targeted strategies to support learners in navigating complex information and improving their comprehension proficiency in academic and real-world scenarios.